2014
DOI: 10.1074/jbc.m114.557231
|View full text |Cite
|
Sign up to set email alerts
|

Physiological IgM Class Catalytic Antibodies Selective for Transthyretin Amyloid

Abstract: Background: Some antibodies express serine protease activity. Transthyretin misfolding causes accumulation of pathogenic amyloid. Results: Constitutively produced IgM but not IgG class antibodies selectively hydrolyzed and dissolved misfolded transthyretin without hydrolyzing physiologically folded transthyretin. Some IgMs were oligoreactive with amyloids and superantigens. Conclusion: Catalytic IgMs may clear misfolded TTR and delay amyloidosis. Significance: The innate antibody repertoire is a source of sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 96 publications
0
57
0
1
Order By: Relevance
“…Importantly, degradation by catabodies should not elicit an inflammatory response. A recent study reported physiologic IgM class catabodies that degrade misfolded soluble and particulate forms of transthyretin (Table 1), but not the physiological form, suggesting a protective function of such catabodies against TTR amyloidogenesis 185 . The same lab recently engineered catabodies capable of degrading aggregated Aβ 186 (Table 1).…”
Section: Strategies To Target the Process Of Protein Aggregationmentioning
confidence: 96%
“…Importantly, degradation by catabodies should not elicit an inflammatory response. A recent study reported physiologic IgM class catabodies that degrade misfolded soluble and particulate forms of transthyretin (Table 1), but not the physiological form, suggesting a protective function of such catabodies against TTR amyloidogenesis 185 . The same lab recently engineered catabodies capable of degrading aggregated Aβ 186 (Table 1).…”
Section: Strategies To Target the Process Of Protein Aggregationmentioning
confidence: 96%
“…In addition, the production of innate amyloid-directed catabodies is not limited to the A␤ target. Healthy humans synthesize catabodies specific for transthyretin amyloid, which is responsible for age-associated systemic amyloidosis (19). Humans produce no more than 100,000 non-antibody proteins, including enzymes and receptors expressing specificity for diverse biological ligands.…”
Section: Discussionmentioning
confidence: 99%
“…The A␤ species mass (monomers, oligomers, and proteolytic fragments) was computed by comparison with reference proteins (1.4 -27 kDa and 14 -97 kDa ladders; Bio-Rad). Oligomer disappearance was monitored by densitometry of the SDS-stable trimer, tetramer, and high mass oligomer bands (45 kDa band, 64 -84 kDa smear) following staining of gel blots with a mixture of mouse anti-A␤ monoclonal IgG 6E10, IgG 4G8 (both from Covance, Princeton, NJ), and IgG 6D4 (MyBioSource, San Diego, CA) (directed to A␤ (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), A␤ (17)(18)(19)(20)(21)(22)(23)(24), and the A␤ C terminus, respectively). Freshly dissolved A␤42 without prior oligomerization was mixed immediately with the nIgVs (3 g/ml) to test the nIgV effect on oligomer accumulation over 24 h of incubation at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this natural clearance of immune complexes can lower the deleterious secondary effects such as inflammation and infiltration of various molecules of the immune system. Catalytic antibodies are described both in physiology as well as under various pathological conditions, such as asthma, hemophilia A, multiple sclerosis, rheumatoid arthritis, Hashimoto's thyroiditis, sepsis, graft versus host disease in transplantation, and others (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Depending on the target antigen, both pathogenic and beneficial role of catalytic antibodies have been described (10,19).…”
Section: Introductionmentioning
confidence: 99%